Implementation of Integrated Quality Strategic Management of Islamic Perspective Education - Erick Yusuf; Hasbi Indra; Maemunah Sa’diyah (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to describe the implementation of integrated quality strategic management of Islamic education perspective. The method used in this research is a literature study by collecting (material materials) sourced from various books, journals, and other sources. The results of the study indicate that the application of strategic management of integrated quality of Islamic education perspective is that the existence of Islamic educational institutions will be advanced and qualified if the management system implements TQM which in its operation is full of the concept of ihsan as a whole. The implementation of TQM must of course be preceded by quality planning or ihsan planning. The planning is actually an application of intentions or something to be realized and desired. Then this quality planning is broken down in benchmarking. Benchmarking is an activity to set standards, both processes and results to be achieved within a certain period. For practical purposes, the standard is reflected from the existing reality.